Epidemiological characteristics of COVID-19 patients of tertiary care hospital of Western Rajasthan - S. L., Mathur; Harish, Agrawal; Afzal, Hakim; Arvind, Jain; Naveen, Kishoria; Rimplejeet, Kaur; Arun, Barath; Veeram, Parmar; K., Goyal Krishna; Sandeep, Tak (International Journal Of Community Medicine And Public Health, 2020)
Background: COVID – 19 is a pandemic that originated from Wuhan, China in the end of 2019. The objective of the present study is to report the epidemiological and clinical features of COVID-19 patients of tertiary care hospital of Western Rajasthan, India. Methods: A total of 1632 cases of COVID-19 were investigated. The patients tested positive by RT-PCR assay were included in the study. The data was obtained from medical record forms of the patients. Results: Out of total patients, 63.42% patients were male and 81.06% of patients were below age of 50 years. The mean of age was 34.93 ±17.61 years and median of age was 32 years. Asymptomatic patients or patients with mild symptoms constituted 66.66% of the study population and 35% of patients had comorbidities. The major comorbidities included diabetes mellitus (2.81%), hypertension (1.59%) and pulmonary diseases (1.04%). Total 40 deaths occurred so the overall CFR was 2.45%. Among the 40 deaths, the mean of age was 57.57±15.67 years. Patients over 50 years of age had the highest CFR among the age groups (18.93%). The CFR for males was 2.34% and for females 2.68%. A total of 14 (35.00%) of patients had multiple comorbidities. Conclusions: The findings of our study emphasize the significant impact of old age and multiple comorbidities on the risk of mortality among COVID-19 patients. It is suggested to take adequate preventative measures more seriously in elderly patients. Also regarding medical care, it is vital to pay special attention to elderly patients with comorbidities.